2021
DOI: 10.4103/jfmpc.jfmpc_2613_20
|View full text |Cite
|
Sign up to set email alerts
|

Empowering adolescents as peer-educators for early prevention of non-communicable diseases

Abstract: Background: Human lifestyles, including sedentary activities, obesity, and smoking, are associated with a high risk of non-communicable diseases that are a leading cause of death globally. Accordingly, health promotion should be done as early as possible in the adolescent period. Aims: This study explores the efficacy of a peer-educator program in promoting the healthy habits of adolescents, via an existing Indonesian community initiative program called ‘POSBINDU’ (Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Almost half of the respondents answered that maintaining a healthy lifestyle becomes less important when they are already on medication. This finding is in contrast with another study that most of the population prefers a healthy lifestyle rather than medication [39][40][41] Our findings align with another study's results, which indicated that individuals diagnosed with lifestyle-related diseases often neglect their dietary and exercise habits. This behavior might come from their perception that medication therapy holds greater significance than diet and exercise that they may believe for relying on medications can make up for their unhealthy lifestyle choices [42].…”
Section: Knowledge Attitude Practice On Hypertension Among Respondentssupporting
confidence: 64%
See 1 more Smart Citation
“…Almost half of the respondents answered that maintaining a healthy lifestyle becomes less important when they are already on medication. This finding is in contrast with another study that most of the population prefers a healthy lifestyle rather than medication [39][40][41] Our findings align with another study's results, which indicated that individuals diagnosed with lifestyle-related diseases often neglect their dietary and exercise habits. This behavior might come from their perception that medication therapy holds greater significance than diet and exercise that they may believe for relying on medications can make up for their unhealthy lifestyle choices [42].…”
Section: Knowledge Attitude Practice On Hypertension Among Respondentssupporting
confidence: 64%
“…Health education strategies that can be implemented are counseling sessions and interactive workshops, increasing self-care skills for blood pressure control action for the hypertensive patient [ 38 ]. Healthy lifestyle education and consultation can be improved and maximized by using various media and ensuring easy access to information and education in POSBINDU [ 41 , 54 ]. Improving the attitude and practice aspect of regular physical exercise can be conducted by including physical programs such as aerobic training, or cooking sessions in the POSBINDU activities.…”
Section: Discussionmentioning
confidence: 99%
“…Explanations of the cotinine test also faced challenges for their acceptance at school due to concerns about the results being reported to the school. Therefore, we collaborated with the representatives of the students and the student council, who were recruited as cadres of Posbindu (Pos Binaan Terpadu/Eng: empowerment program to provide screenings for school communities), to ensure the important information related to the tests reached all students in each class 24 . The cadres were then trained once in each school to provide necessary information regarding the survey and the details of the cotinine test to their classmates.…”
Section: Roles Of the Representatives Of The Student Council And Cadresmentioning
confidence: 99%
“…One effort to prevent hypertension complications, especially heart and blood vessel disease at PHC, is through integrated services (Pelayanan Terpadu or PANDU), such as empowering the community in early detection and monitoring of hypertension risk factors held in the community. Such as implementing a healthy lifestyle starting from the family, controlling hypertension risk factors with early detection and modification of lifestyle, and participating in and supporting efforts to prevent and control hypertension [2].…”
Section: Journal Of Public Health Sciences (Jphs)mentioning
confidence: 99%